Entre silêncios, nódoas e cobiça: homossexualidades masculinas, dominação e transgressão em O Barão de Lavos, de Abel Botelho e Bom-Crioulo, de Adolfo Caminha - Santos, Rivaldo Pereira dos (2012)
Along our study we discuss the construction of the protagonists of two narratives: O Barão de Lavos (1891), by the Portuguese writer Abel Botelho, and Bom-Crioulo (1895), by the Brazilian writer Adolfo Caminha. In both narratives, male homosexuality and hibridity are negatively portrayed through the naturalist perspective, being classified as abnormal and dangerous since they oppose the objectives of the civilizing project that would be implemented in Brazil and in Portugal. Thus, comparative readings of both novels allow us to recognize the way socially rejected masculinities as well as hybridity were integrated to the optic of colonial desire proposed by the civilizing project of the 19th century. In this way, in both narratives homosexuality appears attached to the (hybrid) baron of Lavos and to the (black) Bom Crioulo as marks of rejection and marginalization generally imputed to any sexuality or race opposed to the heterosexual model. Even the genetic formation of both characters made it impossible for them to participate of the future republican project desired by Portugal and Brazil. The very negative markers that were imputed on these two literary figures because of social, cultural and political reasons, masqueraded as genetic heritage, were the reasons for the development of our alternative reading of these narratives, an analysis that used cultural studies and gender studies as its theoretical foundations. In respect to the heterocentrist and white model recognized in several naturalist narratives, which here aimed, through the voice of narrators, to identify the Baron and Bom-Crioulo as transgressors, in our study we indicate the possibility of diverse expressions of subjectivity, showing how different these can be from the narrow limits offered by the imposed hegemonic culture. This space for a different reading came through the oscillations and ambiguities present in voice of naturalist narrator.